Integrated friction torque and thermal model for grease-lubricated rolling bearings under radial load - Takahama, Marcos Hiroshi (2025)
This thesis develops two developed models: a model to represent the friction mechanisms in the contact zone and an integrated model to predict friction torque and temperature in greaselubricated deep groove ball bearings, considering their interdependence. For validation, four models were analyzed: two for friction torque estimation, a thermal model, and an integrated model that couples them. The friction torque model was initially developed based on an adaptation of the SKF model, adjusted for a specific bearing and grease combination. In parallel, a second model was developed to describe the physical behavior of friction. The results indicated that the adjusted model showed good agreement with experimental data, while the physical model exhibited discrepancies, especially under severe conditions. Significant differences were observed between measurements obtained in a ball-on-disk tribometer and the simplified modeling of the contact zone, considering grease as a non-Newtonian fluid, highlighting challenges in the rheological and tribological characterization of grease lubrication. The thermal model, based on a thermal resistive-capacitive circuit, demonstrated high accuracy in predicting the steady-state bearing temperature, with deviations below 2.6°C. The integrated model, which couples the adjusted friction torque model with the thermal model, allowed the evaluation of the interaction between heat dissipation and friction torque over time. The results showed that the integrated model reproduces the system’s behavior in both steadystate and transient conditions but does not capture an initial friction peak observed at the beginning of the tests, which influences the temperature rise. This research contributes to the advancement of friction and temperature modeling in grease-lubricated bearings, providing a foundation for further developments in the field.